Postnatal outcome of prenatally-detected "simple" renal cysts: Are they really simple?. (June 2021) - Ng, Jessica; Loukogeorgakis, Stavros; Sanna, Elisabetta; Derwig, Iris; Yu, Christina; Paramasivam, Gowri; Lees, Christoph; Farrugia, Marie-Klaire
Abstract: Background: The majority of simple renal cysts diagnosed postnatally are asymptomatic and rarely require treatment unless they become symptomatic or complex. We hypothesised that prenatally-detected simple renal cysts would have a similar harmless outcome. Aims: To establish the natural history and postnatal outcome of prenatally-diagnosed simple renal cysts. Study design: Single-centre retrospective case-series review (12-year period). Subjects: All patients with prenatally-diagnosed simple renal cysts (defined as a solitary, non-septated, non-communicating cyst in an otherwise normal kidney). Outcome measures: Prenatal and postnatal changes to cyst size, persistence, resolution or modification of diagnosis. Data is presented as the proportion of patients or median (range). Results: 30 cysts were detected (2 bilateral, 26 unilateral) in 28 fetuses (median gestational age of 23 [20–36] weeks). Median maximum diameter was 15 (4–35) mm at initial diagnosis and 17.5 (4–100) mm across all prenatal scans. On follow-up scans diagnosis was modified in 16 (53%) to: multicystic dysplastic kidney (MCDK), dilated duplex kidney, hydronephrosis, urinoma, renal agenesis and adrenal mass. 12 (40%) cysts resolved. 2 (7%) asymptomatic cysts persisted at one year postnatally. Cyst maximum diameter in the modified diagnosis group (21.5 [10−100] mm) was significantly larger than the simple cyst group (12 [4–20] mm) ( P  = 0.03). Conclusions: Our study revealed the challenges of prenatal ultrasound imaging, with modified diagnoses in over half the cases. Kidneys with solitary cysts could evolve into multicystic kidneys or involute completely, which suggests a true alteration in morphology rather than sonographic error. Persistent simple cysts in an otherwise normal kidney, however, resolved spontaneously or remained asymptomatic. Prenatally-detected simple cysts should be monitored with serial imaging. Highlights: Solitary renal cysts diagnosed prenatally may represent evolving renal pathology. Multi-cystic dysplastic kidneys may not appear multi-cystic on initial evaluation. Multi-cystic dysplastic kidneys may change in appearance on serial prenatal imaging. Fetal simple renal cysts persisting postnatally rarely need intervention. Fetal solitary renal cyst warrant follow-up prenatal scans and postnatal evaluation